Knowledge and Attitudes of Families About Covid-19 Prevention in Sipi Village, Sirenja District Donggala - Chely Veronika Mauruh; Resky Anjeli; Alfrida Semuel Ra’bung; Niswa Salamung; Fanny Metungku; Andi Nur Indah Sari (Universitas Bondowoso, 2021)
Introduction: Coronavirus Disease (Covid-19) is one of the cases of mysterious pneumonia. The source of the transmission of this case is still not known for sure, but the first case was linked to a fish market in Wuhan. The results of a preliminary survey conducted by researchers on May 16, 2020 in Sipi village, Sirenja District, Donggala, that there was one Sipi village community who was confirmed as Covid-19 due to close contact with one of the people in Tompe village, Sirenja District, Donggala Regency, who was found to be positive Covid-19. The purpose of this study was to determine the knowledge and attitudes of the public about the prevention of Covid-19. Method: This research method used descriptive methods with a population of 201 and a sample of 67. The samples were determined using the Nonprobability Sampling technique with a purposive sampling approach. Result: The results of this study indicate that the public's knowledge of prevention Covid-19 is quite good with a presentation number of 61.8% and the public's attitude regarding the prevention of Covid-19 is still not good with a percentage of 70.1%. It is hoped that families who already have good knowledge and attitudes in preventing Covid-19 will maintain and optimize their knowledge and attitudes to prevent the spread of Covid-19. Conclusion: Family knowledge regarding the prevention of COVID-19 is in a fairly good category and family attitudes in preventing COVID-19 are in the category of not good enough.